1981
DOI: 10.1017/s0033291700052879
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mental disorders in Camberwell

Abstract: SYNOPSISA two-stage psychiatric survey of a random sample of adults aged 18–64 from Camberwell is described. Agency interviewers carried out the first stage (N = 800), using the shorter form of the Present State Examination (PSE). MRC interviewers, using the full PSE, saw a stratified sample of these (N = 310) in the second stage. A second interview was sought with all those of Index of Definition (ID) level 5 and above at the first interview (‘cases’) and with a random sample of those below that level. 20·9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
156
9
13

Year Published

1983
1983
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 488 publications
(203 citation statements)
references
References 36 publications
25
156
9
13
Order By: Relevance
“…The fact that in studies characterizing sex differences, higher cutting points had better discriminating capacity among women (Tarnopolsky et al 23 , 1979) was also taken into account. In this respect, there is controversy as to whether there are differences between women and men (Bash & BashLiechti 6 , 1974; Bebbington et al 7 , 1981); these differences may be better explained by social factors (Dekker & Webb 9 , 1974). In most societies, due to the roles that women play, they tend to experience more life events, chronic social stresses and receive less social support than men; this greater exposure to risk factors may explain their increased vulnerability to neurotic disorders (Dekker & Webb 9 , 1974; Dohrenwend & Dohrenwend 10 , 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that in studies characterizing sex differences, higher cutting points had better discriminating capacity among women (Tarnopolsky et al 23 , 1979) was also taken into account. In this respect, there is controversy as to whether there are differences between women and men (Bash & BashLiechti 6 , 1974; Bebbington et al 7 , 1981); these differences may be better explained by social factors (Dekker & Webb 9 , 1974). In most societies, due to the roles that women play, they tend to experience more life events, chronic social stresses and receive less social support than men; this greater exposure to risk factors may explain their increased vulnerability to neurotic disorders (Dekker & Webb 9 , 1974; Dohrenwend & Dohrenwend 10 , 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The case-control studies of Brown and his colleagues (Brown and Harris 1978) showed that lower class women in London were at higher risk for clinical depression than those of the middle class, but this difference was concentrated among women in the two class strata who had young children in the home. Curiously, a later study in the same area of London failed to replicate the social class aspect of Brown et alia's work (Bebbington et al 1981). In the Epidemiologic Catchment Area Program, prevalence data showed weak and non-significant relationships of occupation, income, and education, to major depressive disorder in the year prior to the interview (Weissman et al 1991).…”
Section: Depressive Disorder and Socioeconomic Statusmentioning
confidence: 99%
“…Higher rates of emotional distress, pain, tiredness, and mental illness have been found in those with lower rather than higher social positions (Hunt et al, 1985), but for so-called minor psychiatric disorders (largely depression and anxiety) the evidence for a social gradient is less clear. Some studies have found higher rates among those with lower socio-economic status (Kessler, 1994;Bebbington et al, 1981;Hodiamont et al, 1987) while others (Hare and Shaw, 1965;Lin et al, 1989) have found no social class gradient.…”
Section: Introductionmentioning
confidence: 98%